Halogen-bonded liquid-crystalline complexes formed from 4-alkoxyphenylpyridines with iodine and with interhalogens. Issue 11 (1st March 2023) - McAllister, Linda J.; Taylor, James; Pridmore, Natalie E.; McEllin, Alice J.; Whitwood, Adrian C.; Karadakov, Peter B.; Bruce, Duncan W.
Abstract : Strongly halogen-bonded complexes form between 4-alkoxyphenyl-4-pyridines and iodine as well as the interhalogens ICl and IBr. Examples are characterised by single crystal X-ray crystallography and most complexes show a liquid-crystalline SmA phase. Abstract : Strongly halogen-bonded complexes are formed between 4-alkoxyphenyl-4-pyridines and iodine as well as the interhalogen compounds ICl and IBr, and examples of each are characterised by single crystal X-ray crystallography. On heating, all but one of the complexes display a liquid-crystalline smectic A phase, although there is evidence of decomposition as the materials are heated through the mesophase. For such short molecules, the mesophases are rather stable and small-angle X-ray scattering shows that the complexes form a type of antiparallel, head-to-head dimeric arrangement in the mesophase. Quantum chemical calculations at the DFT (M06-2X) and MP2 levels of theory show the complexes to have very high dipole moments (between ≈ 9–12 D) and the mesophase stability of the complexes is rationalised in terms of antiparallel correlations induced by the strong molecular dipoles.